1969
DOI: 10.1017/s0003356100026994
|View full text |Cite
|
Sign up to set email alerts
|

Crossbreeding of sheep under semi-arid conditions

Abstract: Data were obtained on 3028 lambs born during five successive years from 1961 to 1966 at Ras El-Hekma Desert Research Station in the Western Coastal Egyptian Desert. Breed groups involved in the study were Hungarian Merino, Syrian Awassi, native Barki sheep, and nine of their crosses. The characters studied were birth weight, weaning and yearling weights, pre-and post-weaning average daily gain and yearling greasy fleece weight. The effects of breed group, year of birth, sex, age of dam and type of birth on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…The present superiority of the reciprocal crosses over the Oxford and Suffolk breeds was estimated at 17 % which compares fairly well with the 21% and 17% estimates reported by Fahmy, Galal, Ghanem and Khishin (1969) for crosses among Merino, Barki and Awassi sheep but was higher than the 6% estimate reported by Donald et al (1963) for crosses among Blackface and Swaledale breeds. The present superiority of the reciprocal crosses over the Oxford and Suffolk breeds was estimated at 17 % which compares fairly well with the 21% and 17% estimates reported by Fahmy, Galal, Ghanem and Khishin (1969) for crosses among Merino, Barki and Awassi sheep but was higher than the 6% estimate reported by Donald et al (1963) for crosses among Blackface and Swaledale breeds.…”
Section: Changes In Body Weightsupporting
confidence: 78%
“…The present superiority of the reciprocal crosses over the Oxford and Suffolk breeds was estimated at 17 % which compares fairly well with the 21% and 17% estimates reported by Fahmy, Galal, Ghanem and Khishin (1969) for crosses among Merino, Barki and Awassi sheep but was higher than the 6% estimate reported by Donald et al (1963) for crosses among Blackface and Swaledale breeds. The present superiority of the reciprocal crosses over the Oxford and Suffolk breeds was estimated at 17 % which compares fairly well with the 21% and 17% estimates reported by Fahmy, Galal, Ghanem and Khishin (1969) for crosses among Merino, Barki and Awassi sheep but was higher than the 6% estimate reported by Donald et al (1963) for crosses among Blackface and Swaledale breeds.…”
Section: Changes In Body Weightsupporting
confidence: 78%
“…Fahmy et al (1969), in an earlier study of the birth, weaning, yearling weights and the greasy fleece weight of the same flock, considered the f M and £ M as the most promising in the crosses. From the study of the fibre type arrays in the present work, the birthcoat of the £ M might be considered the best combination of the Merino crosses with the Barki.…”
Section: Discussionmentioning
confidence: 99%
“…The animals therefore be valuable for selecting among lambs at were kept in the research station where a crossing an early age, and more especially for deciding programme using combing wool Merino (Ghanem, whether to continue to cross with Merinos. The 1965) had been going on since 1958 to improve the studies of birthcoat fibre type arrays (Goot, 1941), wool production of the local coarse wool Barki also throw new light on the probable course of evo- (Fahmy et al 1969). Parallel to crossing, a selection lution in the coat of sheep.…”
mentioning
confidence: 99%
“…Other researchers (Mavrogenis, 1996;Kumar et al, 2008) have reported that male lambs from different breeds and at any age had higher live weight and better growth performance than females. The reasons for the higher growth rate of male lambs were the sex hormones (Fahmy et al, 1969) and faster skeletal development than in females (Abbas et al, 2010). However, in the experiment of Manso et al (1996) female lambs were born with lower live weight but after weaning at 37 days of age, they grew faster than males.…”
Section: Introductionmentioning
confidence: 99%